Highly reversible zinc metal anode enabled by strong Brønsted acid and hydrophobic interfacial chemistry - Nian, Qingshun; Luo, Xuan; Ruan, Digen; Li, Yecheng; Xiong, Bing-Qing; Cui, Zhuangzhuang; Wang, Zihong; Dong, Qi; Fan, Jiajia; Jiang, Jinyu; Ma, Jun; Ma, Zhihao; et al. (Nature communications, 2024)
Uncontrollable zinc (Zn) plating and hydrogen evolution greatly undermine Zn anode reversibility. Previous electrolyte designs focus on suppressing H 2 O reactivity, however, the accumulation of alkaline byproducts during battery calendar aging and cycling still deteriorates the battery performance. Here, we present a direct strategy to tackle such problems using a strong Brønsted acid, bis(trifluoromethanesulfonyl)imide (HTFSI), as the electrolyte additive. This approach reformulates battery interfacial chemistry on both electrodes, suppresses continuous corrosion reactions and promotes uniform Zn deposition. The enrichment of hydrophobic TFSI – anions at the Zn|electrolyte interface creates an H 2 O-deficient micro-environment, thus inhibiting Zn corrosion reactions and inducing a ZnS-rich interphase. This highly acidic electrolyte demonstrates high Zn plating/stripping Coulombic efficiency up to 99.7% at 1 mA cm –2 ( > 99.8% under higher current density and areal capacity). Additionally, Zn | |ZnV 6 O 9 full cells exhibit a high capacity retention of 76.8% after 2000 cycles. Trace amounts of strong acid can suppress Zn corrosion and promote uniform Zn deposition. Here, the authors use HTFSI to create a hydrophobic micro-environment at the Zn-electrolyte interface, enabling high efficiency and cycling stability.